Species Specificity on Interaction between IgE and FcεRI - Li, Xiangsheng; Wang, Nannan; Zhao, Yang; Zhang, Yanfen; Liu, Zhongcheng (Current Pharmaceutical Biotechnology, 2019)
Allergic diseases are one of the most prevalent diseases at present, it is imperative to understanding the pathophysiology and treatment strategies for allergic diseases. In this process, the binding of IgE and FcεRI on effector cells plays a critical role in triggering allergic reactions. However, the species specificity of the interaction between IgE and FcεRI has not been clearly explained. This review described the characteristics and the interaction mechanism in the allergic reaction of IgE and FcεRI and summarized the species specificity between IgE and FcεRI.
Keywords: immunoglobulin E